Comparison between Two Different DNA Extraction Techniques Taken from Buccal Swabs Suitable for Genetic Analyzer - Al-Sammarraie, Halah Khalid Ibrahim (Al-Nahrain Journal of Science, 2018)
This study aimed to validate two DNA extraction methods collected from buccal cells to gain a genomic DNA and to determine the effect of process time (from collection time to amplification). Total number of 116 buccal swab samples from unrelated healthy volunteers were subjected to DNA extraction by using two methods: modified (phenol chloroform) (Organic) and Prep Filer Forensic DNA Extraction kit. DNA was evaluated according to the: quantity, integrity and suitability for genetic analysis. The DNA yield and purity were measured by Nano drop Spectrophotometer. Organic method was modified from the classical method (addition Dithiothreitol to lysis buffer), The purity average values increased from 1.4 to 1.6 and it had the highest average concentration (73.3ng/µl) while the highest purity was observed in Prep Filer Forensic DNA Extraction kit with average (1.82). Delayed in sample processing effect both quantity and integrity of the extracted DNA. All samples were genetically analyzed at 16 STR with amelogenin (DNA markers) included in the Amp FlSTR® Identifiler™ PCR Amplification Kit panel from Applied Biosystems. Buccal cell swabs were very good source of genomic DNA especially for large population studies.